Pengaruh Asam Amino Glisin dan Histidin Terhadap Nilai Koefisien Selektivitas EKT Polipirol-Glutamat Sebagai Sensor Potensiometrik - Abdul Karim; Damma Salama; Nurwahyuni Ode (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2009)
A research on the effect of amino acids, glycine and hystidine, on the selectivity of Coated Wire Electrode (EKT)-glutamate has been conducted. Membrane consisted of 0.1 M pyrrole; 0.1 M glutamic acid and 0.1 M HClO4. Analysis of the electrode performance was conducted by looking at the Nernstian factor, detection limit, and solution pH. The effect of amino  acids,  glycine  and hystidine,  on measurement  of glutamic  acid can be  studied  by calculating its selectivity coefficient. Results showed that the electrode gave response of the Nernstian value of 30.24 mV/decade in the concentration range of 10-8  – 10-1  M, detection limit of 2.735 x 10-8  M and pH of 3. Amino acids, glycine and hystidine did not affect the performance of EKT-glutamate with the selectivity coefficient of less than 1.Keywords: Coated Wire Electrode (EKT)-glutamate, Nernstian, selectivity